Le regard atterré et l’envol de l’imaginaire - Vidal, Jean-Pierre (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract With the real artificiality, the true "falseness," of his images, Matthieu Brouillard eloquently captures the imagination while deflecting the spectator's regard toward what must be called a reflection on the very essence of photography. His large photos seem to combine what is held out as realistic reporting with a playful staging that refutes this evidence by producing at the same time a "play within a play" of photography and its history.